Reasons why children miss vaccinations in Western Kenya; A step in a five-point plan to improve routine immunization. Issue 34 (9th August 2021) - Agócs, Mary; Ismail, Amina; Kamande, Kenneth; Tabu, Collins; Momanyi, Christine; Sale, Graham; Rhoda, Dale A.; Khamati, Sylvia; Mutonga, Kelvin; Mitto, Bernard; Hennessey, Karen
Highlights: Over 7 days Red Cross volunteers visited 60, 000 homes to find pockets of under-vaccinated children. Health workers and caregivers of unvaccinated children were consulted to elucidate the reasons. Reasons varied based on who was interviewed and how. Civil society and communities can support Ministries in strengthening vaccination programs. The 5-Point Plan developed by American Red Cross can help further engage communities in this effort. Abstract: Global childhood vaccination coverage has stagnated over the past decade and raising coverage will require a collection of approaches since no single approach has been suitable for all countries or situations. The American Red Cross has developed a 5-Point Plan a to geolocate under-vaccinated children and determine the reasons why they miss vaccination by capitalizing on the Red Cross Movement's large cadres of trusted community volunteers. The Plan was piloted in Bobasi sub-county in Western Kenya, with volunteers seeking to conduct a face-to-face interview in all households, visiting over 60, 000 over 7 days. Six pockets of 233 children without a home-based vaccination record or missing an age-appropriate dose of Penta1, Penta3 or measles-containing vaccine were identified. Three activities were carried out to learn why these children were not vaccinated: 1) one-on-one interviews and 2) focus group discussions with the caregivers of the under-vaccinated children and 3) interviews with healthcare workers who vaccinate in Bobasi. Complacency was commonly reported by caregivers during one-on-one interviews while bad staff attitude or practice was most frequently reported in focus group discussions; health staff reported caregiver hesitency, not knowing vaccination due date and vaccine stock-outs as the most common reasons for caregivers to not have their child vaccinated. As reasons varied across the three different activities, the different perspectives and approaches helped characterize vaccination barriers. Civil society organizations working together with the Ministry of Health can provide valuable information for immunization managers to act on.